Development of Google Sites E-Module Based on PBL on Respiratory System to Improve Critical Thinking Skills of Middle School Students - Qoshirotul Fitri; Agung Mulyo Setiawan (Universitas Pendidikan Mandalika, 2026)
Critical thinking skills are essential for students, yet junior high school students often show low levels of these abilities. Previous studies using Google Sites did not integrate the Problem-Based Learning (PBL) model or focus specifically on respiratory system content and critical thinking. This study aims to develop a PBL-based Google Sites e-module on the respiratory system that is valid, practical, and effective in improving critical thinking skills. The development followed the ADDIE model: analyze, design, develop, implement, and evaluate. Data were collected through questionnaires and tests and analyzed descriptively to assess validity, practicality, and effectiveness. Validation results showed the material was highly valid (84.89%) and the media valid (79.47%). Practicality tests based on teacher and student assessments resulted in scores of 94.68% and 92.71%, respectively, indicating the media was very practical. The effectiveness was supported by an independent sample t-test showing significant differences in critical thinking scores between experimental and control classes. The average N-Gain score of 0.67 in the experimental class indicated a moderate improvement, and a Cohen’s d effect size of 1.21 suggested a large impact. This e-module is valid, practical, and effective for science learning, particularly in supporting teachers to implement student-centered learning that fosters critical thinking.